Seroepidemiology of bluetongue disease in Andhra Pradesh, India * - Sreenivasulu, D; Rao, M B Subba (The Indian Journal of Animal Sciences, 2012)
A serological survey involving 976 sera samples from different species of animals was conducted employing C.ELISA. The study revealed the presence of BTV antibodies in 45.71 % of sheep, 43.56 % of goats, 33.11 % of cattle and 20 % of buffaloes. Prevalence of BTV antibodies was more in crossbreeds than in native sheep and cattle. Neutralizing antibodies to 13 BTV serotypes 2, 4, 6, 7, 8, 9, 12, 13, 14, 16, 17, 18 and 19 were detected in different parts of the state. Region-wise seroprevalence was 46.75 % in Rayalaseema, 46.05 % in Telangana and 33.54 % in Costal regions of Andhra Pradesh.